Synthesis and Structure–Activity Relationship Studies of Benzo[b][1, 4]oxazin‐3(4H)‐one Analogues as Inhibitors of Mycobacterial Thymidylate Synthase X. (20th February 2019) - Modranka, Jakub; Li, Jiahong; Parchina, Anastasia; Vanmeert, Michiel; Dumbre, Shrinivas; Salman, Mayla; Myllykallio, Hannu; Becker, Hubert F.; Vanhoutte, Roeland; Margamuljana, Lia; Nguyen, Hoai; Abu El‐Asrar, Rania; et al.
Abstract: Since the discovery of a flavin‐dependent thymidylate synthase (ThyX or FDTS) that is absent in humans but crucial for DNA biosynthesis in a diverse group of pathogens, the enzyme has been pursued for the development of new antibacterial agents against Mycobacterium tuberculosis, the causative agent of the widespread infectious disease tuberculosis (TB). In response to a growing need for more effective anti‐TB drugs, we have built upon our previous screening efforts and report herein an optimization campaign of a novel series of inhibitors with a unique inhibition profile. The inhibitors display competitive inhibition toward the methylene tetrahydrofolate cofactor of ThyX, enabling us to generate a model of the compounds bound to their target, thus offering insight into their structure–activity relationships. Abstract : Optimization campaign : Starting from a previously identified mycobacterial thymidylate synthase X (ThyX) inhibitor based on a benzo[ b ][1, 4]oxazin‐3(4 H )‐one scaffold, a systematic structure–activity relationship study was performed. This led to the discovery of a benzo[ b ][1, 4]oxazin‐3(4 H )‐one analogue with an IC50 value of 0.69 μm . These heterocycles can be used as starting points for the discovery of novel antibacterial agents that act via ThyX inhibition.